PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN - Syafrudin Syafrudin; iwin Arnova; anggi saputra (Universitas Prof.Hazairin,SH Bengkulu, 2021)
This study aims to determine how much influence the Government Internal Control System and Regional Financial Information System on the Quality of Financial Statements. From the calculation results obtained by the multiple linear regression equation Y = 4,168 + 0,283X1 + 0,368X2, where from the equation it can be interpreted that there is a positive influence between the there variables. The value of the correlation coefficient (R) of 0,935 and the coefficient of determination (R2) of 0,874 shows the effect of the Government internal Control System and the Regional Financial Information System on the Quality of Financial Statements at the Bengkulu City Regional Financial and Asset Management Agency is very strong. Constant (a) of 4,168 means that if the Govermment Internal Control System, Regional Financial Information System is equal to zero, the Quality of Financial Statements is 4,168. Regression Coeffient (b1) of 0,283 means that each increase in the value of the Government Internal Control System by 1%, the Quality of Financial Statements increases by 0,283. Regression Coefficient (b2) of 0,368 means that each increase in the value of the Regional Financial Information System by 1%, the Quality of Financial Statements increase by 0,368. Based on the t value obtained in the hypothesis test (t-test) with a confidence level of 95% and degrees of freedom (42-2-1), the Government Internal Control System t-test value is 2,260 ttable 1,68195. The tcount value of the Regional Financial Information System is 3,259 > ttable 1,68195. This means that Ha is accepted Ho is rejected, which means the hypothesis states that the Government Internal Control System and Regional Financial Information System has a positive effect on the Quality of Financial Statements. Based on the Fcount of 135,456 while Ftable 3,24 which means that the Government Internal Control System and the Regional Financial Information System simultaneously influence teh Quality of Financial Statements.